A test of the generalizability of a recently suggested conceptual model for assessment center ratings. Issue 3 (26th May 2016) - Merkulova, Natalia; Melchers, Klaus G.; Kleinmann, Martin; Annen, Hubert; Szvircsev Tresch, Tibor
ABSTRACT: The present study replicated and extended research concerning a recently suggested conceptual model of the underlying factors of dimension ratings in assessment centers (ACs) proposed by Hoffman, Melchers, Blair, Kleinmann, and Ladd that includes broad dimension factors, exercise factors, and a general performance factor. We evaluated the criterion-related validity of these different components and expanded their nomological network. Results showed that all components (i.e., broad dimensions, exercises, general performance) were significant predictors of training performance. Furthermore, broad dimensions showed incremental validity beyond exercises and general performance. Finally, relationships between the AC factors and individual difference constructs (e.g., Big Five, core self-evaluations, positive and negative affectivity) supported the construct-related validity of broad dimensions and provided further insights in the nature of the different AC components.